2017
DOI: 10.22159/ajpcr.2017.v10i7.18083
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Evaluation of Inferior Turbinate Hypertrophy in Adult Indo-Dravidian Patients With Deviated Nasal Septum

Abstract: Objective: Aim of the study was to evaluate the prevalence and significance of inferior turbinate hypertrophy (ITH) in adult indo-dravidian patients with deviated nasal septum (DNS).Methods: Analysis of sinonasal computerized tomography (CT) images of 86 patients having DNS was done during October 2015-December 2016 for evaluation of severity of the associated ITH. Values of maximum width of medial mucosa, bone and total width of the turbinate were measured. Patients with inflammatory or expansile sinonasal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Sahu et al [11] conducted a study in which he concluded that the severity of DNS and the proportion of inferior turbinate hypertrophy are correlated which was similar to that of present study although the severity was not assessed in present study. The co-occurrence of DNS and inferior turbinate hypertrophy was noted majorly.…”
Section: Discussionsupporting
confidence: 84%
“…Sahu et al [11] conducted a study in which he concluded that the severity of DNS and the proportion of inferior turbinate hypertrophy are correlated which was similar to that of present study although the severity was not assessed in present study. The co-occurrence of DNS and inferior turbinate hypertrophy was noted majorly.…”
Section: Discussionsupporting
confidence: 84%
“…However, inflammatory factors can exacerbate this condition, leading to chronic nasal congestion and an increased predisposition to CRS. 34 Concha hypertrophy can manifest as either bilateral or unilateral enlargement. Bilateral concha hypertrophy is commonly associated with both allergic and nonallergic conditions.…”
Section: Concha Hypertrophymentioning
confidence: 99%